1995
DOI: 10.1007/bf00191966
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic bilateral inguinal hernia repair under local anesthesia

Abstract: A case report of the laparoscopic repair of bilateral inguinal hernias performed under local anesthesia with intravenous sedation is presented. The combination of nitrous oxide for peritoneal insufflation and an ultrasonically activated scalpel for dissection made the procedure feasible. It is hoped that this technique can extend laparoscopic surgery to patients who are poor candidates for general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…In a previous publication, we also reported the use of epidural anesthesia in 16 cases [2]. Pendurthi et al [5] described a case of laparoscopic bilateral inguinal hernia repair that was performed successfully under local anesthesia using the TAPP technique. To date, there have been no reports of total extraperitoneal endoscopic hernia repair attempted under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous publication, we also reported the use of epidural anesthesia in 16 cases [2]. Pendurthi et al [5] described a case of laparoscopic bilateral inguinal hernia repair that was performed successfully under local anesthesia using the TAPP technique. To date, there have been no reports of total extraperitoneal endoscopic hernia repair attempted under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Although very popular, one of the main disadvantages of this procedure is the need for general anesthesia in the vast majority of cases [9,10]. One argument for general anesthesia is the potential of carbon dioxide (CO 2 ) insufflating gas to irritate the peritoneum and cause pain and discomfort [12][13][14]. Additional arguments are the limited extraperitoneal working space and the technical complexity of the procedure.…”
mentioning
confidence: 99%
“…In awake patients, nitrous oxide (N 2 O) is a better tolerated insufflation gas than carbon dioxide (CO 2 ) because it has anesthetic properties and lacks the known tendency of CO 2 to irritate the peritoneum [12][13][14][15]. Two prospective randomized controlled trials of N 2 O versus CO 2 for local pelvic laparoscopic procedures found that N 2 O is associated with less postoperative pain [12,14].…”
mentioning
confidence: 99%
“…Laparoscopic surgery for PIH has always been performed with the patient under general anesthesia, with [27] or without caudal epidural analgesia, except for a single patient who underwent laparoscopic repair of bilateral inguinal hernias under local anesthesia with intravenous sedation [85]. The combination of nitrous oxide for peritoneal insufflation and an ultrasonically activated scalpel for dissection made this procedure feasible with local anesthesia [85].…”
Section: Anesthesiamentioning
confidence: 99%
“…The combination of nitrous oxide for peritoneal insufflation and an ultrasonically activated scalpel for dissection made this procedure feasible with local anesthesia [85]. This technique can perhaps be extended to patients who are poor candidates for general anesthesia.…”
Section: Anesthesiamentioning
confidence: 99%